Monitoring Power Usage on Humanoid Robot Wirelessly Using the INA219 Sensor - Ibnu Fauzi; Nuryono Satya Widodo (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
Currently, humanoid robot power measurements are only carried out when there is a robot's movement that is weakened or unable to move optimally. This is considered to be less than optimal in preventing damage/weakness of the robot's movement. The monitoring device is installed on each part of the humanoid robot, namely the hands and feet, then it will send the current and voltage results via the wireless system. The current sensor used is an INA219 type which is calibrated with a resistor. The power supply used is 12.6 V and the resistors for calibration are 15 Ohm, 18 Ohm, 22 Ohm, 39 Ohm, 47 Ohm, 56 Ohm with each resistor having a power resistance of 5W. The INA219 sensor can read the current, voltage, and power values of the resistor even though there are still differences when compared to multimeter measuring instruments. The results of sensor calibration with a resistor will be used as a comparison when monitoring the humanoid robot. NodeMCU ESP8266 as a microcontroller and wi-fi module. The web server can operate properly when there is a connection. Monitoring runs in real-time for 1 second to refresh data. In the results obtained in all tests, all INA219 sensors can work but are less accurate. For smooth wireless communication and in accordance with research objectives.